SWARM observations of equatorial electron densities and topside GPS track losses. Issue 7 (1st April 2015) - Buchert, Stephan; Zangerl, Franz; Sust, Manfred; André, Mats; Eriksson, Anders; Wahlund, Jan‐Erik; Opgenoorth, Hermann
Abstract The SWARM satellites have both upward looking GPS receivers and Langmuir probes. The receivers repeatedly lost track of the L1 band signal in January–February 2014 at postsunset hours, when SWARM was at nearly 500 km altitude. This indicates that the signal was disturbed by ionospheric irregularities at this height and above. The track losses occurred right at density gradients associated with equatorial plasma bubbles and predominantly where the measured background density was highest. The signal showed strong phase scintillations rather than in amplitude, indicating that SWARM might be in the near field of an ionospheric phase screen. Density biteouts, depletions between steep gradients, were up to almost 3 orders of magnitude deep in the background of a more shallow trough centered at the magnetic equator. Comparison between satellites shows that the biteout structure strongly varied in longitude over ∼100 km and has in north‐south steep walls.